2019
DOI: 10.1111/jre.12708
|View full text |Cite
|
Sign up to set email alerts
|

Pyrosequencing of the subgingival microbiome in peri‐implantitis after non‐surgical mechanical debridement therapy

Abstract: Background and Objectives Peri‐implantitis remains a challenge for dental implant therapy, and the prognosis of non‐surgical therapy for peri‐implantitis is unsatisfactory. In order to reveal the impact of non‐surgical mechanical debridement therapy on microbial communities, we investigated the subgingival microbial communities of healthy implants and implants with peri‐implantitis, both before and after the therapy. Material and Methods Subgingival plaques were collected from patients with healthy dental impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
2
15
1
Order By: Relevance
“…The relative abundance of Tannerella and Porphyromonas decreased after nonsurgical treatment for peri‐implantitis, whereas the relative abundance of Rothia increased (Shiba et al, 2021). A study found Porphyromonas and Treponema could be influenced by peri‐implantitis treatment (Nie et al, 2020). Bacterial species belonging to the genera Porphyromonas , Tannerella , Peptostreptococcus , Filifactor , and Desulfobulbus , such as Porphyromonas gingivalis , Tannerella forsythia , Peptostreptococcaceae XIG‐6 nodatum , Filifactor alocis , and Desulfobulbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The relative abundance of Tannerella and Porphyromonas decreased after nonsurgical treatment for peri‐implantitis, whereas the relative abundance of Rothia increased (Shiba et al, 2021). A study found Porphyromonas and Treponema could be influenced by peri‐implantitis treatment (Nie et al, 2020). Bacterial species belonging to the genera Porphyromonas , Tannerella , Peptostreptococcus , Filifactor , and Desulfobulbus , such as Porphyromonas gingivalis , Tannerella forsythia , Peptostreptococcaceae XIG‐6 nodatum , Filifactor alocis , and Desulfobulbus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Peri-implantitis depicted changes in the submucosal microbiome associated with an increased level of dysbiosis in deeper pockets ( Kröger et al, 2018 ). Some studies have also shown that peri-implant diseases presented higher diversity than clinically healthy peri-implant sites, suggesting that specific species in this pathogenesis could impact in an increasing in the Shannon index ( Komatsu et al, 2020 ; Nie et al, 2020 ). Complementary in this sense, a recent consensus report considered that the microbial picture associated with peri‐implantitis should be regarded as incomplete ( Schwarz et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our analysis, the standard-of-care surgery effectively reduced the overall bacterial burden and limited the population of keystone pathogens. In contrast, non-surgical mechanical debridement of peri-implantitis does not alter the subgingival microbial communities, and thus yields less predictable treatment outcomes 37 . Notably, patients with a low-risk PIL profile continues to benefit from superior bacterial burden control over time while the bacterial burden was exacerbated more rapidly in patients with a high-risk PIL profile.…”
Section: Discussionmentioning
confidence: 99%